Air pollution as a risk factor for Cognitive Impairment no Dementia (CIND) and its progression to dementia: A longitudinal study. (February 2022) - Wu, Jing; Grande, Giulia; Stafoggia, Massimo; Ljungman, Petter; Laukka, Erika J.; Eneroth, Kristina; Bellander, Tom; Rizzuto, Debora
Graphical abstract: Highlights: This is the first longitudinal study that has not only investigated the impact of air pollution on cognitive impairment but also its progression to dementia, considering various air pollutants, and death as competing risk events. Long-term exposure to ambient air pollution was associated with a significantly elevated risk for cognitive impairment among older adults. Air pollution almost doubled the risk for dementia incidence among people with cognitive impairment. Abstract: Background and aim: Accumulation of evidence has raised concern regarding the harmful effect of air pollution on cognitive function, but results are diverging. We aimed to investigate the longitudinal association of long-term exposure to air pollutants and cognitive impairment and its further progression to dementia in older adults residing in an urban area. Methods: Data were obtained from the Swedish National Study on Aging and Care in Kungsholmen (SNAC-K). Cognitive impairment, no dementia (CIND) was assessed by a comprehensive neuropsychological battery (scoring ≥1.5 standard deviations below age-specific means in ≥1 cognitive domain). We assessed long-term residential exposure to particulate matters (PM2.5 and PM10 ) and nitrogen oxides (NOx ) with dispersion modeling. The association with CIND was estimated using Cox proportional hazards models with 3-year moving average air pollution exposure. We further estimated the effect of long-term air pollution exposure on the progression of CIND to dementia using Cox proportional hazards models. Results: Among 1987 cognitively intact participants, 301 individuals developed CIND during the 12-year follow-up. A 1-μg/m 3 increment in PM2.5 exposure was associated with a 75% increased risk of incident CIND (HR = 1.75, 95 %CI: 1.54, 1.99). Weaker associations were found for PM10 (HR for 1-μg/m 3 = 1.08, 95 %CI: 1.03–1.14) and NOx (HR for 10 μg/m 3 = 1.18, 95 %CI: 1.04–1.33). Among those with CIND at baseline (n = 607), 118 participants developed dementia during follow-up. Results also show that exposure to air pollution was a risk factor for the conversion from CIND to dementia (PM2.5 : HR for 1-μg/m 3 = 1.90, 95 %CI: 1.48–2.43; PM10 : HR for 1-μg/m 3 = 1.14, 95 %CI: 1.03–1.26; and NOx : HR for 10 μg/m 3 = 1.34, 95 %CI: 1.07–1.69). Conclusion: We found evidence of an association between long-term exposure to ambient air pollutants and incidence of CIND. Of special interest is that air pollution also was a risk factor for the progression from CIND to dementia.